Haloperidol increases false recognition memory of thematically related pictures in healthy volunteers. (7th December 2016) - Guarnieri, Regina V.; Buratto, Luciano G.; Gomes, Carlos F.A.; Ribeiro, Rafaela L.; de Souza, Altay A. Lino; Stein, Lilian M.; Galduróz, José C.; Bueno, Orlando F.A.
Abstract: Dopamine can modulate long‐term episodic memory. Its potential role on the generation of false memories, however, is less well known. In a randomized, double‐blind, placebo‐controlled experiment, 24 young healthy volunteers ingested a 4‐mg oral dose of haloperidol, a dopamine D2 ‐receptor antagonist, or placebo, before taking part in a recognition memory task. Haloperidol was active during both study and test phases of the experiment. Participants in the haloperidol group produced more false recognition responses than those in the placebo group, despite similar levels of correct recognition. These findings show that dopamine blockade in healthy volunteers can specifically increase false recognition memory.